MES Buffer Affects Arabidopsis Root Apex Zonation and Root Growth by Suppressing Superoxide Generation in Root Apex - Kagenishi, Tomoko; Yokawa, Ken; Baluška, František (Frontiers in Plant Science, 2016)
In plants, growth of roots and root hairs is regulated by the fine cellular control of pH and reactive oxygen species. MES, 2-(N-morpholino)ethanesulfonic acid as one of the Good’s buffers has broadly been used for buffering medium, and it is thought to suit for plant growth with the concentration at 0.1% (w/v) because the buffer capacity of MES ranging pH 5.5-7.0 (for Arabidopsis, pH 5.8). However, many reports have shown that, in nature, roots require different pH values on the surface of specific root apex zones, namely meristem, transition zone and elongation zone. Despite the fact that roots always grow on a media containing buffer molecule, little is known about impact of MES on root growth. Here, we have checked the effects of different concentrations of MES buffer using growing roots of Arabidopsis thaliana. Our results show that 1% of MES significantly inhibited root growth, the number of root hairs and length of meristem, whereas 0.1% promoted root growth and root apex area (region spanning from the root tip up to the transition zone). Furthermore, superoxide generation in root apex disappeared at 1% of MES. These results suggest that MES disturbs normal root morphogenesis by changing the reactive oxygen species (ROS) homeostasis in root apex.